How did the characteristics of the growing season change during the past 100 years at a steep river basin in Japan? - Nagai Shin (Public Library of Science (PLoS), 2021)
The effects of climate change on plant phenological events such as flowering, leaf flush, and leaf fall may be greater in steep river basins than at the horizontal scale of countries and continents. This possibility is due to the effect of temperature on plant phenology and the difference between vertical and horizontal gradients in temperature sensitivities. We calculated the dates of the start (SGS) and end of the growing season (EGS) in a steep river basin located in a mountainous region of central Japan over a century timescale by using a degree-day phenological model based on long-term, continuous, in situ observations. We assessed the generality and representativeness of the modelled SGS and EGS dates by using phenological events, live camera images taken at multiple points in the basin, and satellite observations made at a fine spatial resolution. The sensitivity of the modelled SGS and EGS dates to elevation changed from 3.29 days (100 m)-1 (-5.48 days °C-1) and -2.89 days (100 m)-1 (4.81 days °C-1), respectively, in 1900 to 2.85 days (100 m)-1 (-4.75 days °C-1) and -2.84 day (100 m)-1 (4.73 day °C-1) in 2019. The long-term trend of the sensitivity of the modelled SGS date to elevation was -0.0037 day year-1 per 100 m, but the analogous trend in the case of the modelled EGS date was not significant. Despite the need for further studies to improve the generality and representativeness of the model, the development of degree-day phenology models in multiple, steep river basins will deepen our ecological understanding of the sensitivity of plant phenology to climate change.